Contemporary proteomic research on lignocellulosic enzymes and enzymolysis: A review. (January 2022) - Guo, Hongliang; He, Tongyuan; Lee, Duu-Jong
Graphical abstract: Highlights: Researches on isolation of novel strains and enzymolysic process were reviewed. Identification protocols, key enzymes and synergistic interactions were discussed. Strategies for enhancing enzymolysis efficiencies were outlined. Research prospects to reduce costs for lignocellulose hydrolysis were highlighted. Abstract: This review overviewed the current researches on the isolation of novel strains, the development of novel identification protocols, the key enzymes and their synergistic interactions with other functional enzyme systems, and the strategies for enhancing enzymolysis efficiencies. The main obstacle for realizing biorefinery of lignocellulosic biomass to biofuels or biochemicals is the high cost of enzymolysis stage. Therefore, research prospects to reduce the costs for lignocellulose hydrolysis were outlined.